2019
DOI: 10.26623/slsi.v17i4.1773
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Kompetensi Dan Independensi Terhadap Kinerja Auditor Dengan Self Efficacy Sebagai Variabel Mediasi (Studi Empris Auditor Pada Kantor Akuntan Publik Di Semarang)

Abstract: <h1 align="center"> </h1><p>                                                 Abstrak</p><p>Penelitian ini mengenai kinerja auditor akuntan publik di Semarang. Tujuannya adalah menganalisis <em>Self Efficacy </em>dalam memediasi pengaruh Kompetensi dan Independensi terhadap Kinerja Auditor.</p><p>Metode analisis data menggunakan regresi berganda dan uji sobel utuk menguji hipotesis. Populasi dalam penelitan ini adalah auditor pada kantor akuntan publik di Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
(2 reference statements)
1
0
0
Order By: Relevance
“…This shows that the higher the influence of competence, the higher the employee's performance through self-efficacy mediation. This result is the same as the study before by Romadon and Fridatien (2019).…”
Section: Hypothesis Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…This shows that the higher the influence of competence, the higher the employee's performance through self-efficacy mediation. This result is the same as the study before by Romadon and Fridatien (2019).…”
Section: Hypothesis Resultssupporting
confidence: 90%
“…So that there is an influence of competence on self-efficacy. These results are the same as the results of studies Romadon & Fridatien (2019) and Nurmalia & Setiyaningsih (2020).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The study's findings are in line with previous research conducted by Romadon and Fridatien (2019), who concluded that self-efficacy has a positive and significant impact on the performance of auditors. In summary, an individual's self-efficacy influences their levels of job satisfaction and overall performance.…”
Section: Direct Effect Of Self-efficacy On Performancesupporting
confidence: 91%